Management of Hepatic Trauma: An Update - Lang, Min; Dahan, Isaac J.; Ho, Vanessa P.; Kapoor, Baljendra S. (Digestive Disease Interventions, 2018)
Being the largest solid abdominal organ, the liver is the second most commonly injured organ after abdominal trauma. In this review, we discuss the American Association for the Surgery of Trauma's (AAST) liver injury grading system and World Society of Emergency Surgery's triage grading system. Furthermore, we discuss the role of imaging in hepatic trauma, as well as the indications, techniques, and roles of nonoperative and operative management.
Keywords: hepatic trauma; nonoperative management; operative management; imaging; AAST; WSES; hepatic angioembolization; hepatic injury